Atypical Ductal Hyperplasia Bordering on Ductal Carcinoma In Situ: Interobserver Variability and Outcomes in 105 Cases. (April 2017) - Tozbikian, Gary; Brogi, Edi; Vallejo, Christina E.; Giri, Dilip; Murray, Melissa; Catalano, Jeffrey; Olcese, Cristina; Van Zee, Kimberly J.; Wen, Hannah Yong
Background . The clinical implications of the diagnosis of atypical ductal hyperplasia (ADH) and ductal carcinoma in situ (DCIS) are very different. Yet there are "borderline" breast lesions that have characteristics of both ADH and DCIS. We examined interobserver diagnostic variability for such lesions and correlated pathologic features of the lesions with clinical outcomes. Methods . We identified all cases of borderline ADH/DCIS lesions treated at our center from 1997 to 2010. Five specialized breast pathologists blinded to clinical outcomes independently reviewed all available slides from each case and were instructed to classify each as benign, ADH, or DCIS. A majority diagnosis (MajDx) was defined as a diagnosis agreed upon by ≥3 pathologists. Results . A total of 105 women with borderline ADH/DCIS and slides available for review were identified. The MajDx was ADH in 84 (80%), and DCIS in 18 (17%). There were split diagnoses in 3 (3%). MajDx of DCIS correlated significantly with lesion size and nuclear grade. There was diagnostic agreement by all 5 pathologists in 30% of cases, 4 pathologists in 42%, and 3 pathologists in 25%. At a median follow-up of 37 months, 4 (3.8%) patients developed subsequent ipsilateral breast carcinoma (2 invasive, 2 DCIS); all 4 cases had MajDx of ADH. Conclusions . Borderline ADH/DCIS represents an entity for which reproducible categorization as ADH or DCIS cannot be achieved. Furthermore, histologic features of borderline lesions resulting in MajDx of ADH vs. DCIS are not prognostic for risk of subsequent breast carcinoma.